2022
DOI: 10.1002/cam4.4708
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive concerns among adolescent and young adult cancer survivors: A scoping review of current research situations

Abstract: Fertility is a significant concern among adolescent and young adult (AYA) cancer survivors and their caregivers, especially after their completion of cancer treatment programs. Concerns about fertility affect not only cancer patients' psychological well-being, but also all aspects of their medical treatments, including treatment protocol, decision-making, and treatment adherence. In this scoping review, the PubMed, CINAHL, Web of Science, Embase, CNKI, and Wanfang electronic databases were searched according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…9 10 Reproductive concerns have been proven to be prevalent in patients with cancer and are influenced by various factors such as demographic, clinical and psychosocial factors, including age, number of children, family per capita monthly income, fertility intention, social relational quality, fertility preservation and self-disclosure. 11 According to Benedict et al, 9 good psychosocial adaptation was found to be related to lower reproductive concern. The American Psychological Association defines resilience as 'the process of adapting well in the face of adversity, trauma, threats or significant sources of stress'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…9 10 Reproductive concerns have been proven to be prevalent in patients with cancer and are influenced by various factors such as demographic, clinical and psychosocial factors, including age, number of children, family per capita monthly income, fertility intention, social relational quality, fertility preservation and self-disclosure. 11 According to Benedict et al, 9 good psychosocial adaptation was found to be related to lower reproductive concern. The American Psychological Association defines resilience as 'the process of adapting well in the face of adversity, trauma, threats or significant sources of stress'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Demands: Personal (disease prognosis and survival, fertility and breastfeeding, sex life, fertility preservation decisions, spirituality, treatment and support); 3,5,12,17 information support (fertility technology protection, the timing of pregnancy and safety of childbirth); 1,3,17 desire for communication and support, multiple sources of scientific reproductive knowledge 4,10,16 Response Method: Accept reality; 8,14 seek support (medical, information, family and social); 1,2,12 change bad lifestyle; 2,8 distress; 8,14,19 meaning making; 6,8 having hope while suffering; 7,19 women's advice to health care providers 12,16 .…”
Section: Appendix a T A B L E Amentioning
confidence: 99%
“…To provide a better understanding of this issue, a systematic review on reproductive concerns is necessary to summarise the level of reproductive concerns as well as their influencing factors and relevant health-related consequences among patients with breast cancer. Recently, a scoping review has been conducted to evaluate the literature on reproductive concerns among adolescent and adult cancer patients in general, which provides some information on reproductive concerns among cancer patients 29. When it is specific to women with breast cancer, there have been two identified reviews related to reproductive concerns of patients with breast cancer in 2009 and 2012, respectively 10 16.…”
Section: Introductionmentioning
confidence: 99%